Study of the experimental performance of dew point evaporative cooling arrangement for modified fluid flow passages - Patunkar, Prashant; Dingare, Sunil (Frontiers in Mechanical Engineering, 2022)
The satisfactory performance of indirect evaporative cooling techniques (IEC) is governed significantly by structural and design arrangement of heat and mass exchange device. The experimental performance of dew point evaporative cooler has been investigated in the present work with the geometrically modified flow passages for air and water. Conventionally these passages are formed by either flat or corrugated plates. The trapezoidal corrugated plate has been used to form these passages for air and water. The laboratory trials were conducted for the different combinations of intake air temperature, specific humidity and air velocity. The performance in terms of dew point and wet bulb efficiency is presented based on laboratory trials. The experimental results achieved dew point and wet bulb efficiencies ranging between 52% to 82% and 74% to 126% respectively. The geometrically modified flow passages increases heat exchange area for the same volume of similar heat exchange device and achieves increased thermal performance of the proposed cooler.